2022
DOI: 10.3390/nu14153190
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Food Insecurity in Latin America and the Caribbean Countries: A Cross-Sectional Analysis of 13 Countries

Abstract: It is estimated that Latin America and the Caribbean (LAC) is the region with the second highest figures for food insecurity (FI) globally, with a prevalence of 40.9% in the entire region. This cross-sectional study analyzes the household factors associated with FI across 13 LAC countries. We used data from the first round of high-frequency phone surveys, conducted by the World Bank. Approximately 4 out of 10 people in LAC experienced FI during the first phase of the COVID-19 pandemic. FI was positively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, a study conducted in Brazil suggested that after the pandemic restrictions were adopted, including the closure of schools, families with children were less likely to experience moderate to severe food insecurity because of the social programs established at the national level and/or the solidarity of non-profit organizations and private sector efforts that delivered food kits to these families ( 29 ). Another study found that households with more rooms in urban areas were less likely to experience food insecurity, a finding that was possibly related to the socioeconomic level of the household ( 30 ). A study conducted in eight cities in Peru reported that people who lost their jobs during the pandemic had an 82% higher prevalence of food insecurity, which could be due to the greater reduction of the labor force in that country during the year 2020 ( 31 ), a result that is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted in Brazil suggested that after the pandemic restrictions were adopted, including the closure of schools, families with children were less likely to experience moderate to severe food insecurity because of the social programs established at the national level and/or the solidarity of non-profit organizations and private sector efforts that delivered food kits to these families ( 29 ). Another study found that households with more rooms in urban areas were less likely to experience food insecurity, a finding that was possibly related to the socioeconomic level of the household ( 30 ). A study conducted in eight cities in Peru reported that people who lost their jobs during the pandemic had an 82% higher prevalence of food insecurity, which could be due to the greater reduction of the labor force in that country during the year 2020 ( 31 ), a result that is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This may have forced the prioritization of expenses (e.g., food, housing, and transportation) and the use of health insurance, leaving oral health aside, even after vaccination and the lifting of care restrictions. As a result of unemployment, the reduction in family income and the increase in food prices also brought with it a scenario of food insecurity, which affected Peru to a greater extent compared to other Latin American countries [ 38 , 39 ]. Likewise, due to the fear of contagion, especially due to the high rate of excess mortality in Peru [ 40 ], it is possible that both patients and dentists postponed treatments or preventive visits [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, during the pandemic, changes in the eating habits characterized by an increase in the consumption of high-calorie processed foods (sugary drinks, saturated fats and salt) occurred in children due to the low cost of this type of food and beverages and to a decreased parental control over their children's diets [39,45,46]. Moreover, movement restrictions due to social confinement and food insecurity during the pandemic in various regions of the world such as Latin America [47,48] limited the access to fresh and unprocessed foods such as fruits and vegetables, contributing to an inadequate nutrition of the children and, consequently, to an increase in childhood overweight and obesity [49].…”
Section: Discussionmentioning
confidence: 99%